Factors shaping language learning adversity quotient: the impact of family, self-influence, and educational environment - Nguyen Thi Thuy Linh; Phuong Hoang Yen; Tran Ngoc Bao Chau (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study explores the factors shaping the language learning adversity quotient (LLAQ) and examines the interplay between family influence, self-influence, and educational environment influence in fostering resilience in language learning. The research addresses a gap in the existing literature by investigating the factors that are associated with students’ resilience in language learning. A cross-sectional survey was administered to 434 undergraduate students from a university in Vietnam, utilizing a structured questionnaire to assess the impact of these influences. The findings highlight that family influence plays a pivotal role in nurturing resilience, while self-influence is critical in sustaining students’ persistence. Although educational environment influence received a lower rating, it was found to have a significant correlation with self-influence, suggesting an indirect contribution to LLAQ. The study underscores the importance of enhancing familial support and fostering students’ self-agency. Moreover, it suggests that cultivating a supportive educational environment can indirectly bolster resilience by empowering students to take greater responsibility for their learning. The study concludes by advocating for a holistic approach that integrates support from family, personal agency, and institutional structures to strengthen students’ perseverance in language learning.